(untitled) (Per Musi, 2017)
In the late nineteenth and early twentieth centuries, political and social transformations marked Brazil: abolition, immigration, Republic, urban reforms. One of the themes of these reforms was education. Education would elevate Brazil to a civilized nation. In education, music was presented as important and even essential. Music teaching became a concern for musicians and educators. In São Paulo, several methods have been created. Much criticism and discussions followed every emerging method. The purpose of this article is to bring to light some of these pioneering methods as well the criticism, contests and rivalries around them which voiced not only a matter of education, but a contest for social spaces, especially in the educational, scholarly and popular culture.